(untitled) (Journal of the College of Basic Education, 2022)
In this paper we introduce weighting method where this method is used for solving multi-objective linear programming Problem, such that this method transform the multi – objectives problem into single –objective programming form . Also new proposition is constructed for solving multi-objective functions, where this proposition dependent on weighting method and Game theory